1998
DOI: 10.1093/tropej/44.5.300
|View full text |Cite
|
Sign up to set email alerts
|

Neural tube defects and congenital hydrocephalus in the Sultanate of Oman

Abstract: A retrospective study was carried out in Oman to determine the incidence of neural tube defects (NTD) and congenital hydrocephalus (CH) and to identify any possible associations. National data retrieved from hospital records revealed the incidence of NTD in Oman to be comparatively low (1.25 per 1000), but the incidence of CH was much higher than that seen in Western Europe (0.44 per 1000) and was found to be associated with high rates of other congenital anomalies and neonatal death. There were no specific en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
1
7

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 0 publications
5
21
1
7
Order By: Relevance
“…We were not able to confirm the suggestion that there is an increase risk for NTD in children born of consanguineous parents. The possibility that consanguinity could be a risk factor for NTD in a population requires further research (Murshid, 2000;Rajab et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to confirm the suggestion that there is an increase risk for NTD in children born of consanguineous parents. The possibility that consanguinity could be a risk factor for NTD in a population requires further research (Murshid, 2000;Rajab et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Em relação às hidrocefalias, a incidência mundial conhecida é de 0,3 a 1,0/1.000 nascimentos 1,[9][10][11][12][13][14] . No ECLAMC, durante o período entre 1982 a 1998, a incidência registrada de hidrocefalia foi de 0,74/ 1.000 16 .…”
Section: Resultsunclassified
“…A inicidência das hidrocefalias varia de 0,3 a 1,0/1.000 nascimentos 1,9,[10][11][12][13][14] . Essas variações podem estar relacionadas a diferenças étnicas e geográficas, além de diferenças metodológicas, como casuística de base hospitalar ou populacional, inclusão ou não de natimortos e inclusão ou não de hidrocefalias secundária ao DFTN.…”
unclassified
“…Previous reports from Oman revealed that congenital anomalies are a major cause of death and disability in the country [25][26][27]. This could be explained partially by the high degree of consanguineous marriages in the country.…”
Section: Discussionmentioning
confidence: 99%